Determinant Factors of Limited Oxygen Supply at Marsudi Waluyo Hospital during the Covid-19 Pandemic - Suryaningati, Engelbertha Retno; Hanggriyani, Kristiwi; Prawestiningtyas, Eriko (Fakultas Kedokteran Universitas Brawijaya, 2022)
The demand for oxygen in hospitals has been increasing during the Covid-19 pandemic due to oxygen therapy required by most Covid-19 patients. Fulfillment of oxygen supply is related to logistics management. This study aimed to determine the factors affecting the limited oxygen supply at Marsudi Waluyo Hospital, Malang. This research was conducted with a qualitative descriptive method. Data collection was carried out by observing the process of ordering and replacing oxygen cylinders for central oxygen fulfillment at the Facility Maintenance Unit (FMU), reviewing oxygen usage and supply reports, and conducting Focus Group Discussion (FGD) to identify the root of the problem. The FGD respondents consisted of the Head of General Affairs and Administration, the Head of Finance, the Coordinator and Staff of the Facility Maintenance Unit, and the Head of the Inpatient Installation. The root of the problem was compiled using the 5 Whys method and grouped into Man, Material, Money, Method, Machine, Management, and Environment categories. The root of the problem identified was the limited number of human resources in the Facility Maintenance Unit, the procedure for procuring oxygen cylinders that did not include a case of oxygen demand surge, and no oxygen supply other than oxygen cylinders.